Likuiditas, Kecukupan Modal, dan Suku Bunga sebagai Determinan Profitabilitas Bank Syariah: Studi Perbandingan antara BCA Syariah dan BTPN Syariah periode 2015-2025 - Zahratun Naura; Ana Fitria; Teuku Syifa Fadrizha Nanda (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the impact of liquidity, capitas adequacy, and monetary policy rate on profitability at two Islamic banks with different business models and market segments, namely BTPN Sharia and BCA Sharia during the 2015-2025 period. A quantitative comparative research design was employed, utilizing multiple linear regression analysis. The data analyzed consist of is secondary data sourced from official publications of the Financial Service Authority and Central Statistics Agency. The results of this study indicate that BTPN Sharia has significant positive effect of liquidity, the positive insignificant effect of capital adequacy, and negative significanly effect of monetary policy rate on profitability. Whereas at BCA Sharia, liquidity has a significant negative effect on profitability, insignificant negative effect of capital adequacy, and positive insignificant effect of monetary policy on profitability. These results indicate that liquidity, capital adequacy, and monetary policy rate as determinant of profitability varies based on the characteristics of each institution.